2014
DOI: 10.1016/b978-0-12-801415-8.00013-8
|View full text |Cite
|
Sign up to set email alerts
|

Use of Potentiometric Fluorophores in the Measurement of Mitochondrial Reactive Oxygen Species

Abstract: Mitochondrial reactive oxygen species (ROS) are implicated in signal transduction, inflammation, neurodegenerative disorders, and normal aging. Net ROS release by isolated brain mitochondria derived from a mixture of neurons and glia is readily quantified using fluorescent dyes. Measuring intracellular ROS in intact neurons or glia and assigning the origin to mitochondria are far more difficult. In recent years, the protonmotive force crucial to mitochondrial function has been exploited to target a variety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 43 publications
0
64
0
Order By: Relevance
“…Levels of mitochondrial reactive oxygen species (ROS) were measured as the MitoSOX to MTDR fluorescence ratio (see Supplemental Figure 3) to compensate for possible differences in cell geometry and altered membrane potential dependent loading of MitoSOX (24). Figure 2E indicates significantly higher ROS levels in T2D ␤-cells than in normal ␤-cells, when an outlier normal measurement is rejected.…”
Section: Increased Oxidative Stress In T2d ␤-Cellsmentioning
confidence: 99%
“…Levels of mitochondrial reactive oxygen species (ROS) were measured as the MitoSOX to MTDR fluorescence ratio (see Supplemental Figure 3) to compensate for possible differences in cell geometry and altered membrane potential dependent loading of MitoSOX (24). Figure 2E indicates significantly higher ROS levels in T2D ␤-cells than in normal ␤-cells, when an outlier normal measurement is rejected.…”
Section: Increased Oxidative Stress In T2d ␤-Cellsmentioning
confidence: 99%
“…Importantly, MitoSOX redistributes out of mitochondria in response to stimuli that decrease mitochondrial membrane potential [21, 22]. This renders estimation of mitochondrial ROS based on cellular MitoSOX fluorescence semi-quantitative at best.…”
Section: Introductionmentioning
confidence: 99%
“…This is because factors other than mitochondrial ROS affect the total cellular fluorescent signal once mitochondria are depolarized. We found that cellular MitoSOX fluorescence was enhanced when oligomycin was used to prevent ATP synthase reversal from maintaining mitochondrial membrane potential in the presence of an electron transport chain inhibitor [22]. This observation suggests that increased nucleic acid availability (i.e., cytoplasmic RNA and nuclear DNA) following efflux of MitoSOX from mitochondria may modify the fluorescent signal independently of changes in mitochondrial ROS generation (see [22] for a detailed discussion).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations